The e-STROKE Study: The Design of a Prospective Observational Multicentral Study - Kateřina Dvorníková; Veronika Kunešová; Svatopluk Ostrý; Robert Mikulík; Michal Bar (Journal of Cardiovascular Development and Disease)
Introduction: The e-STROKE study is a prospective, multicenter observational study designed to assess the impact of various CT parameters (including e-ASPECT, CT perfusion (CTP), collateral flow status, and the size and location of the ischemic lesion) on the clinical outcomes of patients with ischemic stroke, as evaluated by the modified Rankins Scale (mRS) three months post-stroke. This study also aims to investigate whether the use of multimodal CT imaging increases the number of patients eligible for recanalization therapy. The analysis will integrate data from the RES-Q registry and radiological data from the e-STROKE system provided by Brainomix Ltd. Aims: The primary aim is to determine the predictive value of CT parameters (e-ASPECTS, CTP, collateral vessel status, and ischemic lesion volume and location) on three-month functional outcomes, as defined by the mRS, in patients with non-lacunar stroke following recanalization treatment (IVT and/or MT). The secondary aim is to evaluate whether multimodal CT examination leads to an increase in the number of patients eligible for recanalization therapy. Additionally, this study seeks to assess the specificity and sensitivity of multimodal CT in distinguishing stroke mimics from actual strokes. Methods: This multicenter observational study involves patients with suspected acute ischemic stroke and a premorbid mRS ≤ 4, who are treated with endovascular thrombectomy (EVT), intravenous thrombolysis (IVT), or managed conservatively in stroke centers within the Czech Stroke Research Network (STROCZECH), which is part of the Czech Clinical Research Infrastructure Network (CZECRIN). Data collection includes demographic, clinical, and imaging data variables such as age, sex, ethnicity, risk factors, treatment times (OTT, DNT, and OGT), TICI scores, post-treatment hemorrhage (ECAS II), mRS outcome, stroke etiology, e-ASPECTS, acute ischemic volume (AIV), thrombus length on NCCT, CTA collateral score and collateral vessel density, location of large vessel occlusion, ischemic core, hypoperfusion volume, mismatch ratio and volume, final infarct volume, hemorrhage volume, and MRI in case of negative follow-up NCCT. Conclusions: We anticipate collecting robust clinical and radiological data from approximately 2000 patients across 22 centers over a 12-month period. The results are expected to enhance the precision of diagnostic and prognostic radiological markers in managing acute stroke.